Raça/cor da pele, gênero e Transtornos Mentais Comuns na perspectiva da interseccionalidade - Smolen, Jenny Rose (2016)
Mental disorders cause the largest burden of disability worldwide, and Common Mental Disorders (CMD) cause a significant burden to the community. Brazil has prioritized the health of Black population and the identification of racial disparities in health, yet few studies on mental health exist in Brazil that use race as a variable of analysis. Through a systematic review of the literature, these studies were identified to understand the association between race and mental health. No studies conducted an intersectional analysis of race and gender. The objective of this study is to examine the interaction between race, gender, and CMD in Feira de Santana, BA. This cross-sectional study used a representative sample of the urban population of 15 years or older in Feira de Santana. All those who self-identified as branco, preto, or pardo were included in the analysis. The Self-Report Questionnaire (SRQ-20) was used to determine the presence of CMD. Prevalence ratios for the four race/gender groups (white men, black men, white women, black women) were calculated using a Poisson regression, and an interaction analysis was performed to assess the contribution of the perspective of intersectionality. The results are presented in the form of journal articles. The systematic review is titled “Race/skin color and mental health disorders in Brazil: a systematic review”, and the analytic article is entitled “The perspective of intersectionality in quantitative health research: an analysis of the association between the intersections of race and gender, and Common Mental Disorders.” The systematic review showed that studies on mental health that assessed race often used different screening tools to identify the mental disorder and had small sample sizes of Afro-Brazilians; despite these problems, the overall trend shows a positive association between race and anxiety and/or depression. The results of the analytic article show that Black women had the highest prevalence of CMD of all the four race/gender groups, and even controlling for potential confounders Black women had a significantly higher prevalence of CMD, 2.43 times that of White men. The analysis of interaction shows the value of the intersectional perspective—that the prevalence seen in Black women is greater than would have been expected if examining race and gender separately. Determining the prevalence of TMC according to race and gender, and the association between these is essential to truly understand the racial disparities in CMD and for Brazil to fulfill its constitutional right of health for all.